IoT Based Water Quality Monitoring System for Swimming Pool - Ali Hassan, Muhamad Khairul; Mohd Shukri, Muhamad Naqib; Ahmad Saad, Fathinul Syahir; Sudin, Sukhairi; Basaruddin, Khairul Salleh; Aziz Safar, Muhammad Juhairi; Basah, Shafriza Nisha; Yazid, Haniza; Mat Som, Hanafi; Long, Zhongjie (International Journal of Integrated Engineering, 2025)
A swimming pool is a recreational facility where people relax and refresh themselves. However, maintaining good water quality is essential, as poor water conditions can negatively impact users’ health. In public swimming pools, operators typically rely on manual devices to measure pH and chlorine levels, making it challenging to maintain consistent water quality. This can lead to potential skin irritation and other health issues. Therefore, an automated water quality monitoring system has been developed to continuously track and maintain pool water quality by measuring pH, chlorine concentration, turbidity, and temperature to ensure a safe and comfortable swimming environment. The system was tested on several swimming pools with varying water conditions, evaluating key parameters such as pH, Total Dissolved Solids (TDS), turbidity, and temperature. The analysis of results demonstrates that the developed system effectively and accurately measures these parameters, providing reliable data for maintaining optimal water quality.